PENGARUH POWER TUNGKAI DAN MINAT TERHADAP HASIL BELAJAR SMASH OLAHRAGA BOLA VOLI PADA SISWA KELAS VI SDN MARGAJAYA I - Yan Yan Julian; Khasanah Khasanah; Nursanita Nasution (Akademika, 2020)
This study aims to determine: (1) the differences in student smash learning outcomes with leg power training and those not taught using leg power training, (2) the effect of the interaction between power leg and learning interest on smash learning outcomes in students, (3) differences in smash learning outcomes of students who have high interest in learning taught by power leg training with students not taught using leg power training, (4) differences in smash learning outcomes in students who have low learning interest taught by power leg training with students who are not taught using leg power training. This study uses an experimental method with a 2 x 2 factorial design. The population is grade VI students of SDN Margajaya I, Bekasi City with a total of 50 students. The sample consisted of 27% of the groups having high interest, while 27% of the groups having low interest. The conclusions of the results of the study are: smash learning outcomes of students who get treated with leg power training is higher than students who do not use leg power training. There is an interaction between power leg training with interest in learning towards smash learning outcomes. Smash learning outcomes of students taught using leg power training are higher than students who are taught without using leg power training in students who have high learning interest. Learning Outcomes Students who have low learning interest who are taught using leg power training are lower than those who do not use leg power training.